Photodynamic therapy in endodontic treatment: An integrative review (Research, Society and Development, 2021)
Photodynamic therapy (PDT) is an adjunctive therapy which exist an interaction between a specific light source, a photossensitizing agent and the molecular oxygenation to trigger cell death. This integrative review aimed to evaluate scientific evidence regarding the effectiveness of PDT as a complement for cleaning root canals. Systematic surveys were carried out at LILACS and BBO databases, using the following words: ("photodynamic therapy") OR ("photochemotherapy") AND (endodontics) OR ("endodontic therapy"). The criteria of inclusion were studies using PDT as a coadjuvant for endodontic treatment and studies evaluating PDT effects. Studies did not use any instrument linked to this study purpose, book chapters, conference summaries, national or international reviews and full texts not published in accredited journals were excluded. According to the results, the most used lasers was Diode of low power from 40mW to 100mW, with frequencies between 500 to 810 nm. The range time used in the include studies was 40 to 240s. The most applied frequency was 660 nm. The most used application protocol used methylene blue as photossensitizer. PDT shows promise as an adjunct for conventional endodontic treatment. However, promising results were observed from PDT in endodontic disinfection, future investigations should be carry out, mainly clinical, to define a clear and safe therapeutic protocol for daily clinical practice.